2018
DOI: 10.1007/s00222-018-0827-8
|View full text |Cite
|
Sign up to set email alerts
|

On the fine structure of the free boundary for the classical obstacle problem

Abstract: In the classical obstacle problem, the free boundary can be decomposed into "regular" and "singular" points. As shown by Caffarelli in his seminal papers [C77, C98], regular points consist of smooth hypersurfaces, while singular points are contained in a stratified union of C 1 manifolds of varying dimension. In two dimensions, this C 1 result has been improved to C 1,α by Weiss [W99].In this paper we prove that, for n = 2 singular points are locally contained in a C 2 curve. In higher dimension n ≥ 3, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 19 publications
5
90
0
Order By: Relevance
“…(4) The last part of the statement in the case (n ≥ 3)-(b) corresponds to Theorem 2.13. In [17] we obtain the same result as a simple byproduct of our analysis. In addition, our result on the existence of anomalous points shows that Theorem 2.13 is essentially optimal.…”
Section: Recent Developmentssupporting
confidence: 69%
See 2 more Smart Citations
“…(4) The last part of the statement in the case (n ≥ 3)-(b) corresponds to Theorem 2.13. In [17] we obtain the same result as a simple byproduct of our analysis. In addition, our result on the existence of anomalous points shows that Theorem 2.13 is essentially optimal.…”
Section: Recent Developmentssupporting
confidence: 69%
“…In a recent paper with Serra [17] we showed that, at most points, (2.7) holds with α = 1. However, there exist some "anomalous" points of higher codimension where not only (2.7) does not hold with α = 1, but actually (2.7) is false for any α > 0.…”
Section: Recent Developmentsmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, we recall that the structure of the singular part of the free boundary of minimizers of the obstacle and thin-obstacle problems was studied by several authors; we refer to [5], [6], [23], [16] and [9], for the obstacle problem, and [19], [10] for the thin-obstacle problem. We also note that, the uniqueness of the blow-up and the logarithmic modulus of continuity follow directly by the lograithmic epiperimetric inequality (Theorem 1.10), exactly as in [9,10].…”
Section: 3mentioning
confidence: 99%
“…In a recent paper with Serra [15] we showed that, up to the presence of some "anomalous" points of higher codimension where (30) is false for any α > 0, one can actually prove that (30) holds with α = 1 at most points (these points will be called "generic"). In particular, up to a small set, singular points can be covered by C 1,1 (and in some cases C 2 ) manifolds.…”
Section: Recent Developmentsmentioning
confidence: 99%